2013
DOI: 10.1515/humor-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

From Ice Age to Madagascar: Appreciation of slapstick humor in children with Asperger's syndrome

Abstract: Abstract:The aim of the present study was to examine whether children with Asperger's syndrome differ from typically developing children in the appreciation of and behavioral responses to simple slapstick type humor, in which cognitive requirements that are commonly impaired in autism spectrum disorders are reduced to a minimum. Short slapstick scenes and matched non-humorous control scenes were extracted from popular movies to produce an appropriate humor assessment material. Twenty-four boys with Asperger's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…Thus, individuals with ASD are expected to present limitations in that respect. Although some studies have found no differences between individuals with ASD and other groups in certain types of humour (e.g., Samson & Hegenloh, 2010;Weiss et al, 2013), a study by Emerich et al (2003) which, similarly to our study, asked adolescents with Asperger syndrome or autism with normal intelligence to choose funny endings for a short story, found their abilities to be lacking compared with typically developing adolescents. Performing the Humour Test in RHLB-PL correctly requires understanding of complex language material and noticing funny, implicit elements, and as such presents a challenge to the adolescents with ASD in the study.…”
Section: Discussioncontrasting
confidence: 45%
“…Thus, individuals with ASD are expected to present limitations in that respect. Although some studies have found no differences between individuals with ASD and other groups in certain types of humour (e.g., Samson & Hegenloh, 2010;Weiss et al, 2013), a study by Emerich et al (2003) which, similarly to our study, asked adolescents with Asperger syndrome or autism with normal intelligence to choose funny endings for a short story, found their abilities to be lacking compared with typically developing adolescents. Performing the Humour Test in RHLB-PL correctly requires understanding of complex language material and noticing funny, implicit elements, and as such presents a challenge to the adolescents with ASD in the study.…”
Section: Discussioncontrasting
confidence: 45%
“…Moreover, children with ASD showed incoherence between subjective feelings of amusement and smiling and laughing behavior in a simple but effective humor task (Weiss et al 2013).…”
Section: Emotional Response Incoherence In Asdmentioning
confidence: 99%
“…Grossman et al 2013;Yirmiya et al 1989) or to the facial expression not matching the subjective experience (Legiša et al 2013;Weiss et al 2013) but that it also occurs at an intrapersonal level involving responses from the same system (i.e. expression of emotions).…”
Section: Expressive Incoherence In Asdmentioning
confidence: 99%
“…In the present study, only depression was controlled. Future studies may examine the potential roles of other psychopathology variables that are characterized by deficits in emotion-related skills as well as specific difficulties in understanding humor such as social anxiety and the autism spectrum (e.g., Samson et al 2012;Weiss et al 2013). Finally, the number of regression analyses in the present study is at the limits of what can be tolerated from a statistical point of view.…”
Section: Discussionmentioning
confidence: 99%